Bullying in different contexts - Monks, Claire P.; Coyne, Iain (Cambridge University Press, 2011)
Bullying has a tendency to be associated with aggression between children in the playground, but bullying and abuse can also be observed in other social settings. Bullying in Different Contexts brings together, for the first time, leading international researchers to discuss these behaviours in a wide range of settings, including preschool, school, the home, residential care, prisons, the workplace and cyberspace. The authors provide background to the different contexts, discuss the impact and types of interpersonal aggression and the characteristics of those involved. A final chapter collates the findings from each context to draw conclusions on the similarities and differences between the behaviours, risk factors for involvement and theoretical approaches to explain bullying. This original volume will further our understanding of bullying and inform preventative and intervention work. The authors seek to show how research from diverse settings may inform our understanding of the bullying phenomenon as a whole